The use of social media in the creation of personal learning environment during the #studyfromhome period - Ni Ketut Agusintadewi; Ni Made Mitha Mahastuti; Kadek Agus Surya Darma; Anak Agung Ngurah Aritama (Journal of Education and Learning (EduLearn), 2021)
Due to the Covid-19 outbreak in Indonesia the Government urged students and lecturers to conduct the learning process from home through an online system called #studyfromhome. The architecture undergraduate students in this study were millennial students who used digital technology on a daily basis. This study was conducted to determine the role of social media, as well as millennial students’ preferences and feedback on the use of social media as learning tools to create a personal learning environment (PLE). Questionnaires were distributed online to students of Class of 2017 and 2018, out of whom 115 respondents provided their feedback. The results of the study showed that the students of the Architecture Study Program at Udayana University in Bali were fond of using social media especially audio-visual applications for learning activities. In addition, very positive feedback was also provided in terms of knowledge sharing and creativity, acquisition of information, and submission of assignments. Social media were considered more student-friendly. This condition was relevant to the characteristics of the millennial students who were independent learners, and facilitated the creation of PLE. Dealing with the new approach, the students hoped that social media could be used in a better manner as architecture learning platforms.